Intraluminal capsaicin does not affect fluid and electrolyte absorption in the human jejunum but does cause pain. Issue 2 (1st August 1998) - Hammer, J; Hammer, H F; Eherer, A J; Petritsch, W; Holzer, P; Krejs, G J
Abstract : Background —Stimulation of sensory nerves with capsaicin regulates ion transport in the small intestine in animal experiments. Aim —To investigate whether sensory nerves that are stimulated by capsaicin administration influence fluid and electrolyte absorption in the human jejunum in vivo. Method —Intestinal perfusion studies were performed in 12 healthy subjects using a four lumen tube with a proximal occlusion balloon and a plasma-like electrolyte solution. After an initial control period, 5 (n = 3), 10 (n = 8), or 50 (n = 1) μg/ml capsaicin was added to the perfusate, and this was followed by a final control period. Rates of absorption of water, sodium, potassium, chloride, and bicarbonate were determined in a 30 cm segment of jejunum using a non-absorbable volume marker. Results —At all three concentrations of capsaicin there were no significant changes in water and electrolyte absorption as compared with control periods. Two subjects who received 10 μg/ml and the subject receiving 50 μg/ml experienced crampy abdominal pain. Conclusion —The results do not support the hypothesis that capsaicin sensitive afferent nerves are involved in the physiological regulation of net absorption or secretion across the human jejunal mucosa. Chemical stimulation of these nerves, however, gives rise to abdominal pain.